Simplify the following, expressing your answer with positive index numbers
$\displaystyle
\frac{(-2)^{-3}\times2^{-4}}{2^{-3}}
$
Please show complete working out. Any help will be appreciated!
For even exponents n, $\displaystyle (-a)^n = a^n$.
For odd exponents n, $\displaystyle (-a)^n = -a^n$.
You should also know the properties of exponents, like
$\displaystyle a^m \times a^n = a^{m + n}$
and
$\displaystyle \frac{a^m}{a^n} = a^{m - n}$.
Apply the above to the problem. (I get $\displaystyle -\frac{1}{2^4}$ or $\displaystyle -\frac{1}{16}$ as my answer.)
01